Introductory oceanography - Thurman, Harold V. (Columbus : Merrill Publishing Company, 1988)
n the first edition of this text, my stated objective was to "help the student develop an appreciation for the oceans through an understanding of their physical and biological processes." I had not, how-ever, presented this very worthwhile goal with any great sense of urgency. conducted by the OPEC nations created strong concern about the development of potential oil reserves lying beneath the continental margin. In a more pressing tone, I discussed the investigation of non-polluting, renewable energy sources such as ocean winds, currents, waves, tides, and temperature differences. Political activities were aimed at clearing the way for the mining of manganese nodules from the deep-ocean floor and the establishment of a 200-mile Exclusive Economic Zone by more and more nations.
History of Oceanography -- The Origin of the Earth, its Oceans, and Life in the Oceans -- Marine Provinces -- The origin of Ocean Basins: Theory of Global Plate Tectonics -- Marine Sediments -- Properties of Water -- Air-Sea Interaction -- Ocean Circulation -- Waves -- Tides -- Geology of the Coastal Regions - The Coastal Ocean and Marginal Seas -- The Marine Environment -- Biological Productivity- Energy Transfer -- Life in the open Ocean -- Life on the Ocean Floor -- Humans Interact with the ocean.
Includes index.
Keywords: OCEANOGRAPHY